Surviving nutritional deprivation during development: neuronal intracellular calcium signaling is critical. - Megha; Hasan, G. (International Journal of Developmental Biology, 2020)
Developing cells and tissues in a growing animal need to sense food quality and integrate this information with on-going time-bound developmental programs. The integration of metabolism with development requires cellular and systemic coordination. Work in our laboratory has focused on Ca2+ signaling arising from the release of Ca2+ stored in the endoplasmic reticulum (ER), which triggers store-operated Ca2+ entry. We describe a role for ER-store Ca2+ that operates at the cellular level in various classes of neurons, and eventually drives the systemic coordination required to survive and complete development under conditions of nutritional deprivation. In the model system Drosophila melanogaster, we have developed a paradigm to induce nutritional stress during the larval stage and used pupariation as a read-out for development. Applying the vast genetic tool kit available in Drosophila to this paradigm, we have uncovered novel roles for intracellular Ca 2+ signaling in regulating neuronal activity, at the level of transcription in glutamatergic neurons, and translation in neuropeptidergic neurons. We find that such regulation of cellular processes is critical for integrating information across a neural circuit at multiple levels, starting from the point of sensing systemic and environmental levels of amino acids to finally connecting with neuropeptide secreting neurons, that communicate with the prothoracic gland, an organ that makes the key developmental hormone, ecdysone. This work underscores the importance of ER-store Ca2+ for neuronal health, with consequences for animal development.